Role of Antioxidants to Increase Survival and Viability of Cryopreserved Cord Blood Hematopoietic Progenitor Cells - Makashova, Olena Ye.; Zubova, Oksana L.; Zubov, Pavel M. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):176.